Penentuan persebaran reservoar sandstone dan identifikasi faults menggunakan aplikasi internal atribut seismik; studi kasus Lapangan X , Kanada - Ranggi Sinansari; Dr. Esmar Budi M.Si; Freddy Yulisasongko M.Si (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2014)
Internal seismic attribute has been uses anylisis for 3D seismic data on the X Field, Basin Nova Scotia, Canada. This analysis aims to make a map the distribution of reservoir sandstone, which is associated with the deposition environment and identification of faults. Seismic attributes are used in the interpretation of reservoir sandstone are the RMS amplitude, maximum amplitude, minimum amplitude while for faults identification is instantaneous frequency and instantaneous phase. Tuning thickness analysis done first before running the attributes per existing seismic horizon to determine the thickness of the horizon sanstone that will be made surface attribute. Further, the log analysis performed elektrofasies with each well. With the context of depositional environment, we can know the distribution of reservoir sandstone , especially in Missisauga formation and san 5 target. It is implies that the distribution of sandstone is very clear in all map attributes especially on amplitud attribut. Key words: Attribute, amplitud, instataneous frequency, instataneous phase, elektrofasies log.